Social policy : an introduction - Blakemore, Kenneth, 1948-; Warwick-Booth, Louise (Maidenhead : Open University Press, 2013)
An overview of developments in social policy and welfare, this text offers chapters on social security, education, health, housing and environment, and community care. The history and principles of British social policy are also included.
Previous edition: 2007.
Includes bibliographical references and index.
Keywords: Social policy; United Kingdom -- Social policy